(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
Stratigraphically important conodonts occurring in the Anisian/Ladinian boundary interval are preliminarily described and their evolutionary lineages discussed. Among them some new taxa are proposed. Gondolella constricta postcornuta ssp. n., G. fueloepi, sp. n. with two new subspecies, G. liebermani Kovacs & Krystyn sp. n. and G.? praehungarica sp. n. Two of the new ones, G. constricta postcornuta and G. ?praehungarica are recognized as zonal index forms in the Balaton Highland Middle Triassic.